Penentuan kerapatan inokulum Xanthomonas campestris pv. campestris dengan spektrofotometer=Determination of Inoculum Densities of Xanthomonas campestris pv. campestris with Spectrophotometer - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The inoculum densities of bacterial plant pathogens are able to be determined with plate-count technique or turbidity measurements. The first ones is used for counting the life cells of bacteria